(untitled) (Jurnal Bahasa, 2019)
The speech text can be considered as a perfect discourse with the existence of a semantic linkage between the textual components. Discourse markers allow the sentences in the paragraphs to be well organized to provide a continuity to the information and make it easy to understand. Therefore, this paper aims to uncover the various elements of discourse markers and the rationale behind their usage in the 2019 Budget speech text. This speech was the first budget speech for the new coalition party, Pakatan Harapan. This research is a descriptive study using qualitative methods. The concept of anaphoric adverbs (Asmah, 2008) and the theory of Functional Grammar (Halliday & Matthiessen, 2014) have been employed in this research. Based on the results of the study, there are various types of discourse elements used by the speaker in the text of 2019 Budget Speech. The extension link, adverbs of purpose and the benefits adverb are seen as three elements of discourse that are often used in the production of the text of his speech. However, the text of this speech is also full of other discourse markers. The collaboration of discourse markers shows that connectors play an important role in ensuring the textuality of the 2019 Budget speech and can create contextual, structured speeches that are easily accpeted by language users. Keywords: discourse marker, anaphoric adverb, speech text, functional grammar, 2019 Budget